Discovery of the bound state of three gluons - odderon - V. E. Aushev (Ядерна фізика та енергетика)
The TOTEM collaboration at the Large Hadron Collider, together with the D0 collaboration at the Tevatron collider at Fermilab, have announced the discovery of the odderon – a bound state of three gluons that was predicted about 50 years ago. The result was presented at CERN on March 5 and follows the joint submission in December 2020 of a CERN and Fermilab preprints by TOTEM and D0 reporting this observation. States comprising several gluons are usually called “glueballs”, and are peculiar objects made only of the carriers of the strong force. The advent of quantum chromodynamics led theorists to predict the existence of the odderon, C-odd gluonic compound. Proving its existence in high-energy collisions at Tevatron and LHC has been a major experimental challenge. The work is based on a model-independent analysis of data at medium-range momentum transfer. The TOTEM and D0 teams compared proton-proton data (recorded at collision energies of 2.76, 7, 8, and 13 TeV and extrapolated to 1.96 TeV), with Tevatron proton-antiproton data measured at 1.96 TeV. In agreement with theoretical predictions, the proton-proton cross-section exhibits a deeper dip and stays below the proton-antiproton cross-section until the bump region, thus evidence of odderon was found.